Reward Systems and Ultra-processed Foods. - Nour Rezaieg (Al-Anbar Medical Journal)
Indeed, the prehistoric period was associated with chronic malnutrition, which was a fundamental rule of human history. Because of this, natural selection favored genetic patterns that could survive in these harsh conditions by storing fat. This is because the main function of body fat is to store food reserves for the body [1]. Feeding behavior could be an interaction of a physiologic need for food with the reward system that powerfully encourages excessive eating in some people. Neuroadaptations in the reward system happens when people eat too many tasty foods. This disconnects eating behavior from caloric needs and leads to uncontrollable overeating [2]. Over time, body fat became a major issue. However, the negative effects of being overweight were not recognized in medical literature until as late as the 18th century. Then, technological advancement and economic prosperity resulted in the comfortable availability and simple cost of high-calorie foods, which are palatable to a large segment of the population [3].      Many factors that were formed as a result of this technological development have become major contributors to the increase in the obesity epidemic, including the increased use of sugar substitutes, the addition of preservatives to foods, sugar-sweetened beverages, changing eating patterns, as well as the promotion of sedentary lifestyles [4].      Excess calories taken in comparison to calories burned from any source result in the accumulation of these calories as body fat. Obesity may be characterized in many ways: For starters, it is a condition in which excess body fat interferes with normal activity and health. Second, the weight is more than 20% greater than the ideal height and body size. Third, a body mass index (BMI) is over 30. [5].